Microplastic effects on soil nitrogen storage, nitrogen emissions, and ammonia volatilization in relation to soil health and crop productivity: mechanism and future consideration - Sarfraz, Umair; Qian, Yinsen; Yu, Qiaoqiao; Cao, Yifan; Jiang, Xiaoyi; Mahreen, Nida; Tao, Rongrong; Ma, Quan; Zhu, Min; Ding, Jinfeng; Li, Chunyan; Guo, Wenshan; et al. (Frontiers in Plant Science, 2025)
Microplastic contamination in agricultural soils is emerging as a significant environmental challenge due to its detrimental effects on soil health, nitrogen cycling, and crop productivity. This review paper synthesizes current knowledge on the impacts of various microplastics, specifically polyethylene (PE), polyvinyl chloride (PVC), and polypropylene (PP), on agricultural systems, with a particular focus on their interactions with nitrogen dynamics and ammonia volatilization processes. Microplastics enter agricultural soils through multiple sources, including plastic mulching, irrigation, and application of biosolids, leading to alterations in soil physical and chemical properties, nutrient availability, and microbial activity. These changes negatively influence critical soil processes such as nitrogen mineralization, nitrification, and denitrification, thereby reducing nitrogen use efficiency (NUE) and increasing ammonia volatilization. Consequently, these disturbances manifest in reduced crop growth and productivity, particularly affecting crops such as wheat. This review also explores biochar as a promising remediation strategy, highlighting its potential to mitigate microplastic-induced disruptions in soil ecosystems by improving soil structure, enhancing nitrogen retention, and reducing ammonia emissions. However, the paper identifies significant knowledge gaps, including the need for standardized methodologies and long-term field studies to understand the cumulative impacts of microplastics comprehensively. To address microplastic pollution effectively, integrated approaches combining scientific research, sustainable agricultural practices, and robust policy frameworks are recommended. This will ensure agricultural sustainability, soil fertility, and food security amidst growing environmental concerns.